Diagnosis of Malaria: A Lab‐On‐chip Tool for Rapid, Quantitative, and Stage‐selective Diagnosis of Malaria (Adv. Sci. 14/2021). Issue 14 (21st July 2021) - Giacometti, Marco; Milesi, Francesca; Coppadoro, Pietro Lorenzo; Rizzo, Alberto; Fagiani, Federico; Rinaldi, Christian; Cantoni, Matteo; Petti, Daniela; Albisetti, Edoardo; Sampietro, Marco; Ciardo, Mariagrazia; Siciliano, Giulia; et al.
Abstract : In article 2004101, Marco Giacometti, Riccardo Bertacco and co‐workers reported on a diagnostic tool (TMek) based on paramagnetic properties of hemozoin nanocrystals in infected red blood cells (i‐RBCs). Exploiting the competition between gravity and magnetic forces, i‐RBCs in a whole blood specimen are sorted and electrically detected in a microchip. The findings indicate the potential of TMek as a quantitative, stage‐selective, rapid test for malaria. Cover designed by Tommaso Pravettoni and Jonathan Barsotti.